Intracardiac thrombotic complications - Okreglicki, A (SA Heart Journal, 2017)
Any patient with a prosthetic valve should have a malfunction of the valve actively excluded if he presents with any new or worsening symptoms of cardiac failure and new arrhythmias. This is even if another cause seems obvious, such as poorly controlled atrial fl utter in this case, and despite apparent normal prosthetic valve auscultatory fi ndings. (2) Unless the anticoagulation levels are known to have been stable in the therapeutic range, if a procedure is to be done that may be associated with an increased risk of thromboembolism, screening for intracardiac thrombosis is indicated.